Review of Printed Electrodes for Flexible Devices - Li, Quanling; Zhang, Jiayan; Li, Qianhao; Li, Guihong; Tian, Xiyue; Luo, Zewei; Qiao, Fei; Wu, Xing; Zhang, Jian (Frontiers in Materials, 2019)
Printed electronic technologies draw tremendous attention worldwide due to their ability to surpass the limitations of traditional high-cost electronics, based on rigid silicon, and the manufacturing of various devices on flexible substrates. As a critical component of flexible electronics, electrodes fabricated on soft, bendable, and stretchable substrates are of great importance. Based on the fabrication process, this paper classifies the mainstream technologies into two categories: top-down and bottom-up. Top-down technologies include physical evaporation methods, printing technologies and soft lithography, while bottom-up technologies involve polymer-assisted-metal-deposition methods and ion-exchange methods, respectively. In contrast to top-down technologies that transfer functional ink onto substrates directly, the bottom-up method achieves a great improvement in the adhesion between substrates and metal electrodes. In this paper, the challenges of top-down technologies, including cost, synthesis, and choice of ink for printing technologies, the limited choice of metal for bottom-up technologies and the mass production of these methods, are also discussed.